DIGITAL TRANSFORMATION AND THE BANKING MARKET: FRIEND OR FOE? A COUNTRY-LEVEL STUDY - Khan, Noureen A.; Ahmed Khattak, Mudeer (Bank Indonesia, 2024)
Countries’ digital transformation continues and yet the impact on the banking sector is unknown. This uncertainty might become even worse if banks start to compete among themselves to get ahead of digital lending and payment platforms. Competition among banks leads to lower lending rates and increased deposit rates. These smaller margins might lead to instability in the banking sector. We address the impact of digital transformation and bank competition on banking sector stability by looking at country-level data from 48 Asian economies. We integrate the moderating role of bank competition into the picture. The findings suggest that digital transformation leads to banking sector stability while bank competition results in banking sector fragility. During high competition within the banking sector, digital transformation lessens the overall banking sector stability and as competition declines, the relationship moves towards insignificance after falling below a moderate level of competition. These findings carry important policy implications. Countries should have control over banking sector competition and should at the same time move towards digital transformation to achieve larger goals like financial inclusion. Lower competition helps to avoid any negative impacts from digital transformation in a country.